On the Accentuation of the Earliest Latin and Romance Loanwords in Slavic - Matasović, Ranko (2007)
The paper discusses the earliest Latin and Romance loanwords in Slavic, including many Roman toponyms preserved in Croatian.
Projekt MZOS
ENG